Stock Transformation: Understanding the Impact of Stock Split on Company Performance in Indonesia Stock Exchange through Before and After Comparative Analysis - Jayanti, Vira Ardhia Pramesthi; Pinem, Dahlia (Jurnal Multidisiplin Madani, 2024)
The study delves into the differences in stock price, trading volume activity, and security return variability of stock splits policy, which is a corporate action where companies increase the number of outstanding shares while reducing their nominal value. This quantitative study analyzed 66 companies listed on the Indonesia Stock Exchange that underwent a stock split between 2017-2022. This research employs the Wilcoxon Signed Rank Test through SPSS 28 to explore the transformation in stock prices, trading volume activity, and security return variability before and after stock splits. The study presents significant findings: (1) there are noticeable differences in stock prices before and after stock splits, (2) trading volume shows variations before and after the corporate event, and (3) there are notable disparities in security return variability before and after stock splits. This study provides valuable insights for investors, analysts, and corporate strategists by examining the complex dynamics of stock splits and their impact on stock prices, trading activity, and security returns